Pembelajaran Holistik-Reflektif melalui E-Modul Interaktif Berbasis Nilai Islam pada Materi Larutan Penyangga - Fikriyah, Miftahul; Wulandari, Wulandari; Nazhifah, Siti; Rahmasari, Tri Padilla (Entalpi Pendidikan Kimia, 2025)
In Islamic schools, the teaching of Chemistry and other sciences as well must go beyond an integrated approach to embedding the spiritual and the scientific awareness. Despite this, there remain situations where science is taught without considering its religious value. This research intends to develop interactive e-modules integrating Islamic values with STEM for the reflective and whole learning experience focused specifically on buffer solutions. This research employs a mixed-methods approach using descriptive quantitative and reflective qualitative methods to measure the effectiveness of said e-modules. This includes the cognitive, affective, and reflective aspects of 30 students from XI IPA class at MAN 2 Pekanbaru. Cognitive data were obtained from a post-test conducted on Quizizz, while affective and reflective data were obtained from questionnaires and open-ended questions. The students' post-test scores (M = 81.00), which significantly exceeded the minimum passing grade of 75 (t = 2.167; p = 0.0386), were indicative of the positive outcome of the intervention. The affective data also evidenced students’ spiritual awareness and emotional engagement in lessons greatly (M = 4.2; SD = 0.9). Students' reflective results were able to demonstrate the concept of a buffer system in relation to the balance of God’s creation and vital elements in life. These findings confirm that the integration of science and spirituality through interactive e-modules can build a holistic, meaningful, and relevant learning character for 21st-century education.